2021
DOI: 10.3389/fnins.2021.657693
|View full text |Cite
|
Sign up to set email alerts
|

White-Matter Repair as a Novel Therapeutic Target for Early Adversity

Abstract: Early adversity (EA) impairs myelin development in a manner that persists later in life across diverse mammalian species including humans, non-human primates, and rodents. These observations, coupled with the highly conserved nature of myelin development suggest that animal models can provide important insights into the molecular mechanisms by which EA impairs myelin development later in life and the impact of these changes on network connectivity, cognition, and behavior. However, this area of translational r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 90 publications
(176 reference statements)
1
5
0
Order By: Relevance
“…Abnormal myelination is one of the most consistent findings in individuals exposed to early deprivation, with similar findings reported in nonhuman primates and rodents [ 82 ]. Only a few studies have examined the effects of LB on myelin development [ 47 , 83 ], and the mechanisms responsible for these changes are yet to be clarified.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Abnormal myelination is one of the most consistent findings in individuals exposed to early deprivation, with similar findings reported in nonhuman primates and rodents [ 82 ]. Only a few studies have examined the effects of LB on myelin development [ 47 , 83 ], and the mechanisms responsible for these changes are yet to be clarified.…”
Section: Discussionsupporting
confidence: 77%
“…4 ) suggests that other factors also contributed to reduced myelination. Since myelination is driven by neuronal activation [ 82 ], it is possible that the impoverished conditions associated with LB cause abnormally low levels of neuronal activation in perforant pathway terminals that further impair OPC differentiation. In addition, recent work has shown that LB reduces the expression of sodium channels in OPC located in the developing hippocampus [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of an increase in FC and myelination in the corpus callosum ( 78 ) reflects normal cerebral development in rats, and these changes typically continue well into adulthood (3–6 mo) but were impaired in sham and depression control animals. It is well established that exposure to early life stress alters WM development in humans, nonhuman primates, and rodents ( 79 ). In addition, abnormal myelination has been reported in human patients with depression and animal models of depression and anxiety-like behaviors ( 15 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“… 14 Myelination and improved microstructural organization of white matter pathways continue throughout childhood and into young adulthood, ultimately allowing for improved signal transduction and communication between distal brain regions among cognitive and emotional systems. 15 , 16 , 17 Studies have found that air pollution is associated with smaller white matter surface area in children, 11 increases in myo-inositol, a brain metabolite involved in cell membrane and myelination, 18 and reduced fractional anisotropy (FA). 12 , 19 These studies 11 , 12 , 18 , 19 are primarily based on smaller, localized populations, and results may have limited generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…The potential impingement on key neurodevelopmental processes by PM 2.5 exposure may cause lifelong health effects . Myelination and improved microstructural organization of white matter pathways continue throughout childhood and into young adulthood, ultimately allowing for improved signal transduction and communication between distal brain regions among cognitive and emotional systems . Studies have found that air pollution is associated with smaller white matter surface area in children, increases in myo-inositol, a brain metabolite involved in cell membrane and myelination, and reduced fractional anisotropy (FA) .…”
Section: Introductionmentioning
confidence: 99%